Different Like Me : My book of autism heroes - Elder, Jennifer, 1968-; Thomas, Marc. (London : Jessica Kingsley, 2006)
'Different Like Me' introduces children aged 8-12 years to famous, inspirational figures from the world of science, art, maths, literature, philosophy and comedy.
Includes bibliographical references (p. 47-48).
Keywords: Autism -- Patients -- Biography -- Juvenile literature; Autistic artists -- Biography -- Juvenile literature; Non-Fiction 9+.; Personal Issues